All-printed nanomembrane wireless bioelectronics using a biocompatible solderable graphene for multimodal human-machine interfaces - Young-Tae Kwon (Nature Portfolio, 2020)
Though wearable electronics remain an attractive technology for bioelectronics, fabrication methods that precisely print biocompatible materials for electronics are needed. Here, the authors report an additive manufacturing process that yields all-printed nanomaterial-based wireless electronics.